2005
DOI: 10.1136/bjo.2004.053025
|View full text |Cite
|
Sign up to set email alerts
|

Human ganglion cells express the alpha-2 adrenergic receptor: relevance to neuroprotection

Abstract: Background/aim: Alpha-2a adrenergic receptor (a 2 -AR) agonists are thought to be neuroprotective, preventing retinal ganglion cell death independent of pressure reduction. Previous studies have identified a 2 -ARs in rat retina. The authors aimed to demonstrate the presence and localisation of a 2 -ARs in human and rat retina and on the rat retinal ganglion cell line, RGC-5. Methods: Seven postmortem human and three postmortem rat eyes were paraformaldehyde fixed and frozen. RGC-5 cells were also paraformalde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 31 publications
(25 reference statements)
1
36
0
2
Order By: Relevance
“…43 In addition to the IOP-lowering potential, adrenergic agonists seem to have neuroprotective properties and alpha-2 receptors have been found to be present in RGCs. 46 In a rat model where transient ischemia was induced, brimonidine significantly reduced RGC loss. 47 In another study also carried out in rats, administration of brimonidine before inducing ischemia not only decreased RGC death but also sustained retrograde axonal transport.…”
Section: Topical Therapiesmentioning
confidence: 98%
“…43 In addition to the IOP-lowering potential, adrenergic agonists seem to have neuroprotective properties and alpha-2 receptors have been found to be present in RGCs. 46 In a rat model where transient ischemia was induced, brimonidine significantly reduced RGC loss. 47 In another study also carried out in rats, administration of brimonidine before inducing ischemia not only decreased RGC death but also sustained retrograde axonal transport.…”
Section: Topical Therapiesmentioning
confidence: 98%
“…The expression of multiple adrenergic receptor subtypes in taste buds parallels findings in other sensory systems such as the retina (Dong et al , 2007, Kalapesi et al , 2005, Zarbin et al , 1986), the organ of Corti (Fauser et al , 2004, Khan et al , 2007), and the olfactory bulb (Doucette et al , 2007, Ennis et al , 2007, Nai et al , 2009). In each, the expression of both alpha and beta receptors across peripheral receptor cells or output neurons appear to share a common general conclusion: adrenergic receptors play a modulatory rather than primary functional role in sensory stimulation.…”
Section: Discussionmentioning
confidence: 54%
“…Alpha-2 adrenergic receptor (A2R) is systemically distributed and its subtypes are pharmacologically defined as 2A/D, 2B and 2C [15,16]. It was revealed that the a-2A receptor is expressed in the GCL and inner nuclear layer of the mammal retina, possibly involving the regenerative effect of A2A directly on the RGCs [17]. The retinal localization of other subtypes of A2R, however, has not yet been well investigated.…”
Section: Discussionmentioning
confidence: 99%